Role of multi-detector computed tomography in the detection and differentiation of adnexal mass lesions - Khalda, Ezzat; Rahman, Hafizur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of this study was to evaluate the role of multi-detector computed tomography (MDCT) in the detection and differentiation of adnexal masses using post-operative histopathology findings as the gold standard. Methods: One hundred and forty five cases that were referred with a primary diagnosis of adnexal masses on clinical or USG examination were evaluated by MDCT in the Department of Radiodiagnosis from January 2013 to December 2013. One hundred twelve cases subsequently underwent surgical exploration and histopathological examination, which was used as a control for the evaluation of MDCT findings, were included in this study. Results: Majority (54.5%) of the patients were in the age group of 31-50 years. MDCT detected adnexal masses as malignant in 56 cases, while in other 56 cases it read adnexal masses as benign. Final histopathology revealed adnexal masses in 57 (51%) cases as malignant while in 55 (49%) cases as benign. There were three cases which on MDCT appeared as malignant were subsequently found to be benign in histopathology. Similarly there were four cases which on MDCT appeared as benign were subsequently proved to malignant in histopathology. The sensitivity, specificity, Positive predictive value and negative predictive value of MDCT for diagnosing a malignant adnexal mass was 93.0%, 94.5%, 94.6% and 92.8% respectively. MDCT findings more predictive of malignancy were solid or cystic-solid mass, necrosis in a solid lesion, cystic lesion with thick, irregular walls or septa, and/or with papillary projections. The presence of ascites, peritoneal metastases, and lymphadenopathy were also helpful to confirm malignancy. Conclusions: MDCT is an excellent and accurate non-invasive modality in the detection and characterization of adnexal masses from benign and malignant